A Group of Reliefs from the Mramba Village (the Republic of Abkhazia): To the Question of Dating - Ekaterina Yu. Endoltseva (Anastasis: Research in Medieval Culture and Art, 2019)
Article deals with a group of reliefs from the church in Mramba village. Their were dated by the paleochristian period. New findings of the last ten years permit to adjust this version. They can be now referred to the Medieval period (10 – 11 century).